Effect of pre-germinal treatment and temperature on the germination of achenes of Baccharis dracunculifolia DC - Santos, R. F. [UNESP]; Amaro, A. C. E. [UNESP]; Carmo, E. L. [UNESP]; Ramo, A. R. P. [UNESP]; Buso, D. R. [UNESP]; Nascimento, W. M.; Silva, P. P.; Rosseto, M. (Int Soc Horticultural Science, 2019)
The species Baccharis dracunculifolia, known as alecrim-do-campo is very rough, of great economic importance, recommended for recovery of degraded areas, but is little explored by propagation through seeds. In order to understand aspects of reproductive biology of B. dracunculifolia of achenes, this study aims to verify the influence of pre-germination treatment and the influence of different germination temperatures in the performance of seed germination. The seeds were placed in translucent germination boxes, with four replicates of 30 seeds for each treatment. Germination was carried out with pre-germination treatment stratification (5 degrees C) for 0, 1, 2, 3, 4 and 5 days, with a photoperiod of 14 h with light and 10 h in dark, in a germination chamber B.O.D. The 15 degrees C treatment was carried out with 0, 1, 2, 3, 4 and 5 days with pre-germination treatment stratification (5 degrees C) and successively for all treatments. After this period, the same photoperiod of 15, 20, 25, 30 and 35 degrees C remained. The germination was evaluated for 30 days, considering the number of germinated seeds; those showing radicle protrusion of less than 2 mm, the speed index, the average time and average speed of germination. The temperature of 20 degrees C without pre-germinative treatment provided 17.8% of germination. The highest speed of germination was obtained at 30 degrees C with pre-germination treatment stratification (5 degrees C) for 4 days. The temperature of 35 degrees C inhibited germination and there was no significant effect on mean germination time. The pre-germinating treatment for three days, combined with the temperature of 20 degrees C, provided a higher average speed of germination. Thus, it appears that the pre-germination treatment stimulated germination of achenes, suggesting that longer periods of chill accumulation increased seed germination subjected to high temperatures.
Keywords: alecrim-do-campo; cold treatment; seeds; reproductive biology; stratification